Soil quality in an experimental agricultural area using Pfeiffer chromatography - Coaracy, Thiago do Nascimento; Melo, David Marx Antunes de; Almeida, Gessica Caitano de; Giovannini, Lume Fajardo; Diniz, Belísia Lúcia Moreira Toscano (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
Rational soil management and diagnosis are crucial and must be considered when planning sustainable agricultural production. Therefore, the objective with this research was to evaluate the evolution of soil quality through Pfeiffer’s Chromatography after the use of agroecological practices in an experimental system. The work was carried out in the municipality of Bananeiras, Paraíba, in an experimental subsystem with Noni planting (Morinda citrifolia), located on the first floor of the Center for Human and Agricultural Sciences at the Federal University of Paraíba Three soil samples in the 0-20 cm layer were collected in the field and taken to the Agroecology laboratory to perform the practice of Pfeiffer Chromatography. The chromatogram interpretation process was used, verified during the use of agroecological practices such as application of biofertilizer, green manure and soil monitoring in the subsystem. As a result, chromatograms before agroecological practices obtained sufficient soil health, whereas for soil chromatograms after agroecological practices there was an improvement for all areas of chromatography. Therefore, agroecological practices provided improvements in soil quality and life and Pfeiffer’s chromatography was essential to diagnose soil health.